Copper and manganese containing chabazite SCR catalysts for N2O reduction

By using CHA skeleton type copper manganese aluminosilicate catalyst, its components are adjusted to improve activity and selectivity, the problems of low-temperature NOx conversion performance and high-temperature stability in the prior art are solved, and efficient and stable NOx conversion effect is achieved.

JP2025510040APending Publication Date: 2025-04-14UMICORE AG & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024556263
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2023-03-23
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

The prior art lacks the selective reduction performance of nitrogen oxides (NOx) under low temperature conditions, and the stability of SCR catalysts in high temperature and water vapor environments is poor.

Method used

The crystalline copper-manganese aluminosilicate catalyst with CHA skeleton type is used to improve the activity and selectivity of the catalyst and enhance its stability in high temperature and water vapor environment by adjusting the content of copper and manganese and the silicon ratio (SAR value) of aluminum.

Benefits of technology

It achieves efficient conversion of NOx under low temperature conditions, and the stability of the catalyst in high temperature and water vapor environments is significantly improved, meeting the demand for NOx conversion and emission control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510040000013
    Figure 2025510040000013
  • Figure 2025510040000014
    Figure 2025510040000014
  • Figure 2025510040000015
    Figure 2025510040000015
Patent Text Reader

Abstract

The present invention discloses a catalytically active composition comprising a crystalline aluminosilicate zeolite having a CHA framework type, the zeolite having an SAR value of 7-25, a copper content of 3.0%-4.5% by weight, a manganese content of 0.3%-4.0% by weight, the copper and manganese being calculated as CuO and MnO based on the total weight of the zeolite, and the sum of the molar amounts of copper and manganese divided by the molar amount of aluminum being in the range of 0.11-0.96. These catalytic substrate monoliths can be used in processes for removing nitrogen oxides from combustion exhaust gases and they can be part of an emission treatment system.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention uses a small 2 The present invention relates to catalytically active compositions for the selective catalytic reduction of nitrogen oxides from exhaust gases of combustion engines exhibiting O emissions. In particular, the present invention relates to chabazite supported with copper and manganese. Methods for producing these catalytically active compositions and their uses are also envisaged. [Background technology]

[0002] Zeolites are vertex-shared TO 4 Zeolites are crystalline microporous aluminosilicate materials formed by tetrahedra, where T represents silicon (Si) or aluminum (Al), interconnected by oxygen atoms to form pores and cavities of uniform size and shape precisely defined by the crystal structure. Zeolites are also called "molecular sieves" because the pores and cavities are similar in size to small molecules. This class of materials has important commercial applications as adsorbents, ion exchangers and catalysts.

[0003] Zeolites are classified by the International Zeolite Association (IZA) according to the rules of the IUPAC Commission on Zeolite Nomenclature. Once a new framework topology is established, a three-letter code is assigned. This code defines the atomic structure of the framework and can then explain distinct X-ray diffraction patterns.

[0004] It is also common to classify zeolites according to their pore size, which is defined by the ring size of the largest pore opening. Zeolites with large pore size have a maximum ring size of 12 tetrahedral atoms, zeolites with medium pore size have a maximum pore size of 10, and zeolites with small pore size have a maximum pore size of 8 tetrahedral atoms. Well-known small pore zeolites belong in particular to the AEI, CHA (chabazite), ERI (erionite), LEV (levin) and KFI framework types. An example with large pore size is the faujasite framework type zeolite.

[0005] A large number of molecular sieve structures are known today. Some known molecular sieves belong to specific families of structures with similar characteristics. One particular family, the ABC-6 family, can be described as a stacking of two-dimensional periodic layers of unconnected planar six-ring motifs, composed of six T atoms (T=Si, Al, etc.) connected by oxygen atoms. The resulting layers, with hexagonal symmetry, are also called periodic building units (PerBUs). The stacking is typically described by a sequence of letters "A", "B", and "C", which indicate the relative positions of adjacent layers. "A", "B", and "C" refer to the well-known relative positions of adjacent layers when stacking hexagonal layers of close-packed spheres.

[0006] The CHA framework belongs to the ABC-6 family and can be described by a repeating stacking sequence of AABBCC, which results in a framework topology characterized by a three-dimensional eight-ring pore system containing double six-membered rings (d6R) and cha cages.

[0007] Small pore zeolites, especially when cations such as copper and iron are contained in the zeolite pores, play an important role as catalysts in the so-called Selective Catalytic Reduction (SCR) of nitrogen oxides with ammonia to form nitrogen and water. The SCR process has been widely used to purify exhaust gases resulting from the combustion of fossil fuels, especially from stationary power plants and vehicles powered by diesel engines.

[0008] NH 3 By NO x The catalytic reduction of NO can be represented by different reaction equations. Nitric oxide (NO) is the main NO produced in the engine. x The reduction of NO is the "standard" NH 3 - Called SCR reaction: 4NO+4NH 3 +O 2 →4N 2 +6H 2 0 (1)

[0009] NO 2 is more reactive than NO. NO and NO 2 In the presence of a mixture of 3 -SCR reactions are more facile and are the so-called "fast" NH 3 -SCR reactions may occur: 2NH 3 +NO+NO 2 →2N 2 +3H 2 O (2)

[0010] high speed NH 3 -To get the benefit of the SCR reaction, an additional catalyst converts some of the NO into NO 2 It is useful for oxidizing to

[0011] Also, side reactions can occur resulting in undesirable products or unproductive consumption of ammonia. 4NH 3 +3O 2 →N 2 +6H 2O (3) 2NH 3 +2O 2 →N 2 O+3H 2 O (4) 4NH 3 +5O 2 →4NO+6H 2 O (5) 4NH 3 +7O 2 →4NO 2 +6H 2 O (6) 2NH 3 +2NO 2 +H 2 O→NH 4 NO 2 +NH 4 NO 3 (7)

[0012] In certified driving cycles, fuel consumption is reduced and CO 2 The exhaust gas temperatures of the latest generation of low-emission engines and hybrid vehicles are significantly lower than those of previous engine generations. x Show conversion rate NH 3 It is necessary to obtain a -SCR catalyst. In general, Cu-containing zeolites have better low-temperature NO than their Fe-containing counterparts. x The conversion rate is shown. 3 -SCR catalysts use as little N as possible. 2 During the conversion of NOx by copper-promoted SCR catalysts in the exhaust gas systems of diesel engines in on-road and off-road applications, the greenhouse gas N 2 O is formed as a by-product. This is due to the NO 2 This is more pronounced at higher contents.

[0013] NH 3 -Next to selectivity and activity, the hydrothermal stability of the SCR catalyst is another essential parameter, since it should withstand harsh temperature conditions under full engine load and exposure to water vapor at temperatures up to 700 °C is known to be critical for many zeolite types.

[0014] WO 2021 / 219628 A1 discloses an SCR catalyst comprising a substrate, which may be a flow-through substrate or a wall-flow filter, and a coating dispersed on the substrate. The coating comprises a first non-zeolitic material comprising aluminum, an 8-ring pore zeolitic material selected from CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX and LTA, which comprises one or more of copper and iron, and a second non-zeolitic oxide material comprising cerium and one or more of zirconium, aluminum, silicon, lanthanum, niobium, iron, manganese, titanium, tungsten, copper, molybdenum, neodymium, cobalt, chromium, tin and praseodymium; at least 65% by weight of the coating is made of an 8-ring pore zeolitic material comprising one or more of copper and iron. Most preferably, the zeolitic material is CHA. The coating comprising cerium and zirconium oxide has lower back pressure and better NO 2 emission than other coatings tested. x It has been shown that the conversion rate is 2 No O selectivity testing was performed.

[0015] WO 2018 / 081682(A1) provides a catalyst composition comprising a zeolite having an LTA structure with iron, manganese or a combination thereof as an extra-framework metal. The zeolite may have an SAR value of 15-70 and contain 0.5 wt%-10 wt% iron, manganese or a combination thereof. Optionally, the catalyst composition may be used with a second catalyst composition comprising a second molecular sieve selected from AEI, AFX, CHA, or LTA with an extra-framework metal selected from antimony, bismuth, cesium, chromium, cobalt, copper, iron, manganese, molybdenum, nickel, niobium, tin, titanium, tungsten, vanadium, zinc, zirconium, and combinations thereof. Fresh Mn-LTA and aged Mn-LTA have better NO2 reduction than fresh and aged Mn-CHA and Mn-AFX. x Conversion rate and lower N2 However, the large pore zeolite Mn-BEA showed better NO2 peaks at about 150 to about 200 °C than all three Mn-containing small pore zeolites. x yielded the conversion rate.

[0016] China Patent Publication No. 111375445(A) discloses a method for preparing a molecular sieve denitration catalyst supported by manganese. The molecular sieve-supported manganese-based denitration catalyst is prepared by mixing a molecular sieve, a soluble aqueous solution of a manganese salt and a ligand to form a mixed solution, in which the molecular sieve has an opposite electrical property to the complex formed by the manganese salt and the ligand, and carrying out electrostatic adsorption and other processes on the mixed solution. The molecular sieve-supported manganese-based denitration catalyst has a uniform particle size of the active component and a uniform distribution on the support surface, and is particularly suitable for removing nitric oxide. The molecular sieve can be selected from many molecular sieves, and AEI, CHA, FAU and ZSM are preferred. In an embodiment, Mn-supported CHA is synthesized and subjected to sulfur aging. The sulfur-aged Mn-CHA showed a lower light-off temperature of NH3-SCR reaction and better NOx conversion rate than Mn-CHA obtained by conventional liquid ion exchange method. The molecular sieve according to China Patent Application Publication No. 111375445(A) does not contain any other transition metals other than manganese, and is a sieve containing N 2 The formation of O was not investigated.

[0017] H Xue, X Guo, T Meng, Q Guo, D Mao and S Wang: "Cu-ZSM-5 Catalyst Impregnated with Mn-Co Oxide for the Selected Catalytic Reduction of NO: Physicochemical Property-Catalytic Activity Relationship and In Situ DRIFTS Study for the Reaction Mechanism", ACS Catal 2021, 11, 7702-7718, impregnated Cu-ZSM-5 with copper and manganese, reduced NO at temperatures below 200°C. 3 -SCR catalytic activity was shown to increase. The Cu-ZSM-5 zeolite used had a Cu / Al ratio of 38, corresponding to a SAR value of 76, and a copper content of 1.98 wt.%. The zeolite was impregnated with manganese and cobalt, and the mass ratio of Mn to Co in the zeolite thus impregnated was varied from 1:0.5 to 1:5. The total amount of (Mn+Co) remained constant at 10 wt.% Cu-ZSM-5.

[0018] C Song, L Zhang, Z Li, Y Lu and K Li: "Co-Exchange of Mn: A Simple Method to Improve Both the Hydrothermal Stability and Activity of Cu-SSZ-13 NH3-SCR Catalysts", Catalysts 2019, 9, 455-469, a series of Cu-Mn-SSZ-13 were obtained by co-exchange of Mn and Cu into SSZ-13 and compared with Cu-SSZ-13 catalyst in selective catalytic reduction (SCR) of nitric oxide (NO) with ammonia. The aim was to simultaneously improve the low-temperature activity of the catalyst and its resistance to hydrothermal aging. The higher the copper content of SSZ-13 with CHA framework structure, the higher the low-temperature activity but the lower the hydrothermal stability. Zeolite SSZ-13 with SAR values ​​was ion-exchanged with copper and optionally manganese. The obtained zeolites have Mn / Cu molar ratios from 0 / 10 (Cu only) to 6 / 10. The degree of ion exchange of the zeolite thus obtained was calculated as mole Cu (or Mn)x2 / mole Alx100% based on the results of inductively coupled plasma atomic emission spectroscopy (ICP-AES). The degree of ion exchange of Cu was in the range of 0.35 (Mn / Cu ratio = 0 / 10) to 0.13 (Mn / Cu ratio = 6 / 10), and the degree of ion exchange of Mn was in the range of 0 (Mn / Cu ratio = 0 / 10) to 0.17 (Mn / Cu ratio = 6 / 10). This corresponds to a Cu / Al ratio of 0.175 (Mn / Cu ratio = 0 / 10) to 0.065 (Mn / Cu ratio = 6 / 10) and a Mn / Al ratio of 0 (Mn / Cu ratio = 0 / 10) to 0.085 (Mn / Cu ratio = 6 / 10). The (Cu+Mn) / Al ratio was in the range of 0.15–0.175. The NO conversion, NO oxidation, and NH oxidation of these catalysts were excellent. 3 Oxidation and NH 3 The desorption and desorption of the catalyst was investigated. The catalyst called Cu(0.2)Mn(0.1) showed the highest reactivity in the low temperature range and the best resistance to hydrothermal aging. This catalyst had a Mn / Cu ratio of 6 / 19, a degree of Cu ion exchange of 0.2, a degree of Mn ion exchange of 0.1, a Cu / Al molar ratio of 0.1, a Mn / Al molar ratio of 0.05, and a (Cu+Mn) / Al molar ratio of 0.15.2 O formation was not investigated.

[0019] J Du, J Wang, X Shi, Y Shan, Y Zhang and H He: “Promoting Effect of Mn on In Situ Synthesized Cu-SSZ-13 for NH 3 -SCR", Catalysts 2020, 10, 1375-1388, NH of in situ synthesized Cu-SSZ-13 3 The effect of Mn impregnation on the -SCR activity was investigated. All Cu-SSZ-13 catalysts had a copper content of 4.6 wt% and a Si / Al ratio of 4.8, corresponding to an SAR value of 9.6. The Cu-SSZ-13 catalysts were impregnated with 0, 3, 5, 7, 10 and 14% Mn. The NH 3 -SCR catalyst activity, N 2 Selectivity and N 2 O formation was investigated. Among all the catalysts, 5%Mn / Cu-SSZ-13 showed the best catalytic activity in the low temperature range, with nearly 95% NOx conversion at around 140 °C. However, with further increase in Mn content, the low temperature NOx conversion began to decrease when compared with 5%Mn / Cu-SSZ-13. More N 2 O was produced with increasing Mn content, which indicates that the addition of Mn improves the N 2 It was shown that N 2 The O formation was less than 20 ppm for Mn / Cu-SSZ-13 with Mn content less than 7%. 5%Mn / Cu-SSZ-13 performed the best among all the catalysts prepared.

[0020] WO 2020 / 047356(A1) discloses a catalytic composition for treating exhaust gases, comprising a molecular sieve containing exchanged copper and exchanged manganese. In a preferred embodiment, the molecular sieve is selected from AEI, CHA, BEA and MFI. The SAR value is 5-200, most preferably 10-30. The atomic ratio of copper to manganese is 0.1-50, preferably 0.3-3. The copper is present in an amount of 0.1-7% by weight, most preferably 1-4% by weight, and the manganese is present in an amount of 0.05-7% by weight, most preferably 0.5-2.5% by weight. Experiments have been carried out to evaluate the catalytic properties of fresh and aged AEI zeolites in high speed SCR, low speed SCR and standard SCR, as well as N. 2 The effects of copper and manganese content on O selectivity were examined. 2 O selectivity is determined by the N formed 2 moles of O converted to NO x is defined as the moles of NO x NO and NO 2 This is defined as N 2 The lower the O selectivity, the greater the amount of NO converted. x Low N relative to the amount of 2 The amount of copper was kept constant and the manganese content was varied, or vice versa. The AEI zeolite containing copper and manganese showed improved light-off temperature, lower N 2 O selectivity, and NO selectivity equal to or better than that of AEI zeolites containing only copper. x The conversion rate was shown. When the amount of Cu was kept constant and the amount of Mn was increased at the same time, thereby decreasing the Cu / Mn ratio, 2 No significant increase in O selectivity at the light-off temperature x The conversion is particularly improved, which is NO x Conversion rate and N 2This means that there was a proportional increase in NO production. SAR values ​​for the AEI zeolites were not given. AEI with 1.5 wt% Cu and 1.5 wt% Mn performed better than CHA with the same amounts of Cu and Mn. In experiments comparing AEI to CHA, SAR values ​​were not given for either. In experiments with two chabazites, with SAR values ​​of 13 and 22, respectively, both with 1.5 wt% Cu and Mn content each, the CHA with the lower SAR value gave better NO production. x Conversion rate and lower N 2 It was found that BEA and MFI containing either 3 wt.% Cu and 1.5 wt.% Mn, respectively, showed NO selectivity in the case of BEA, and O selectivity in the case of MFI. x The conversion rate is not affected by the presence of Mn, but the BEA containing Cu and Mn has less N than the BEA containing only Cu. 2 In the case of MFI, the zeolite containing only Cu showed better NO formation than the MFI containing both Cu and Mn. x Conversion rate and low N 2 O formation was observed.

[0021] US Patent Application Publication No. 2015 / 078989(A1) describes a method for determining NO in lean combustion exhaust gas. xDisclosed is a catalyst composition useful for the selective catalytic reduction of. The catalyst composition comprises an aluminosilicate material comprising silica and alumina in a CHA framework and having a silica to alumina ratio (SAR) of about 10 to about 25, and about 1 to about 5 weight percent of a base metal ("BM"), based on the total weight of the zeolitic material, the base metal being disposed in the zeolitic material as free and / or extra-framework exchange material, and an alkali metal or alkaline earth metal (collectively "AM") being disposed in the zeolitic material as free and / or extra-framework exchange metal. The base metal is selected from chromium, manganese, iron, cobalt, nickel, copper, and mixtures thereof. The alkali metal or alkaline earth metal is selected from sodium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium. The BM and AM are present in a molar ratio of about 15:1 to about 1:1, respectively. The example shows a SSZ-13 zeolite having a SAR value of 17 and promoted with copper and a second metal which is one of calcium, potassium, magnesium, sodium, cesium or manganese.

[0022] Good NO x It exhibits a high conversion rate, has the lowest possible light-off temperature and at the same time has a low N 2 There is a continuing need for SCR catalytically active compositions that exhibit O selectivity. Summary of the Invention [Problem to be solved by the invention]

[0023] Thus, there is provided a catalytically active composition for removing nitrogen oxides from the exhaust gases of a combustion engine, which exhibits a high conversion rate of nitrogen oxides to nitrogen due to good activity and good selectivity for this conversion, while at the same time exhibiting a low N 2 It is an object of the present invention to provide a catalytically active composition which exhibits NO selectivity and NO / O selectivity. Another object of the present invention is to provide an apparatus and system for treating the exhaust gas of a combustion engine which comprises the catalytically active composition according to the present invention. Yet another object of the present invention is to provide an apparatus and system for treating the exhaust gas of a combustion engine which comprises the catalytically active composition according to the present invention. x The objective is to provide a method for reducing emissions, and optionally also particulate matter. [Means for solving the problem]

[0024] A catalytically active composition for removing nitrogen oxides from the exhaust gases of a combustion engine, which has good activity and therefore a high conversion rate of nitrogen oxides to nitrogen, and good selectivity for this conversion, while at the same time providing a low N 2 The object of the present invention to provide a catalytically active composition exhibiting a selectivity for O is solved by a catalytically active composition comprising a crystalline aluminosilicate zeolite having a CHA framework type, the zeolite having an SAR value of 7-25, a copper content of 3.0 wt.%-4.5 wt.% and a manganese content of 0.3 wt.%-4.0 wt.%, the copper and manganese being calculated as CuO and MnO, respectively, based on the total weight of the zeolite, and the sum of the molar amounts of copper and manganese divided by the molar amount of aluminum being in the range of 0.11-0.96.

[0025] A catalytically active composition for removing nitrogen oxides from the exhaust gases of a combustion engine, which has a high conversion rate of nitrogen oxides to nitrogen due to good activity and good selectivity for this conversion, while at the same time having a low N 2 A catalytically active composition exhibiting O selectivity, as well as an apparatus and a system for treating the exhaust gas of a combustion engine comprising the catalytically active composition, are described below, and the invention encompasses all of the embodiments described below, both individually and in combination with each other.

[0026] The selective catalytic reduction of nitrogen oxides to nitrogen is hereinafter referred to as "SCR" or the "SCR reaction".

[0027] A "catalytically active composition" is a substance or mixture of substances capable of converting one or more components of an exhaust gas into one or more other components. An example of such a catalytically active composition is, for example, an oxidation catalyst composition capable of converting volatile organic compounds and carbon monoxide into carbon dioxide or ammonia into nitrogen oxides. Another example of such a catalyst is, for example, a selective catalytic reduction catalyst (SCR catalyst) composition capable of converting nitrogen oxides into nitrogen and water. In the context of the present invention, an SCR catalyst is a catalyst comprising a support substrate and a washcoat comprising an SCR catalytically active composition. An ammonia slip catalyst (ASC) is a catalyst comprising a support substrate, a washcoat comprising an oxidation catalyst and a washcoat comprising an SCR catalytically active composition.

[0028] Molecular sieves are materials with uniformly sized pores, i.e., very small holes. The diameter of these pores is similar in size to small molecules, and therefore larger molecules cannot penetrate or adsorb, but smaller molecules can. In the context of the present invention, molecular sieves are zeolites. Zeolites are corner-sharing tetrahedral structures of SiO 4 and AlO 4 units. They are also called "silicoaluminates" or "aluminosilicates". In the context of the present invention, these two terms are used synonymously.

[0029] As used herein, the term "non-zeolitic molecular sieve" refers to a corner-sharing tetrahedral framework in which at least some of the tetrahedral moieties are occupied by elements other than silicon or aluminum. When some, but not all, of the silicon atoms are replaced by phosphorus atoms, it is referred to as a "silicoaluminophosphate" or "SAPO". When all of the silicon atoms are replaced by phosphorus, it is referred to as an aluminophosphate or "AlPO".

[0030] "Zeolite framework types", also called "framework types", represent a corner-sharing network of tetrahedrally coordinated atoms. It is common to classify zeolites according to their pore size, which is defined by the ring size of the largest pore opening. Zeolites with large pore sizes have a maximum ring size of 12 tetrahedral atoms, zeolites with medium pore sizes have a maximum pore size of 10, and zeolites with small pore sizes have a maximum pore size of 8 tetrahedral atoms. Known small pore zeolites belong in particular to the AEI, CHA (chabazite), ERI (erionite), LEV (levinite), AFX and KFI frameworks. Examples with large pore sizes are zeolites of the framework type faujasite (FAU) and zeolite beta (BEA).

[0031] A "zeotype" includes any of a family of materials based on the structure of a particular zeolite. Thus, a particular "zeotype" includes, for example, silicoaluminates, SAPOs, and AIPOs based on the structure of a particular zeolite framework type. Thus, for example, chabazite (CHA), silicoaluminates SSZ-13, Linde R, and ZK-14, silicoaluminophosphate SAPO-34, and aluminophosphate MeAlPO-47 all belong to the chabazite framework type. Those skilled in the art know which silicoaluminates, silicoaluminophosphates, and aluminophosphates belong to the same zeotype. Furthermore, zeolites and non-zeolitic molecular sieves that belong to the same zeotype are listed in the database of the International Zeolite Association (IZA). Those skilled in the art can use this knowledge and the IZA database without departing from the scope of the claims.

[0032] The silica-to-alumina ratio of zeolites (SiO 2 :Al 2 O 3 ) is hereinafter referred to as the "SAR value."

[0033] A "catalyst support substrate," also referred to simply as a "support substrate," is a support onto which a catalytically active composition is deposited to form the final catalyst. As such, the support substrate is a support for the catalytically active composition.

[0034] A "washcoat" as used herein is an aqueous suspension of a catalytically active composition and, optionally, at least one binder. Suitable binder materials are, for example, aluminum oxide, titanium dioxide, silicon dioxide, zirconium dioxide, or mixtures thereof, such as a mixture of silica and alumina.

[0035] A washcoat applied to a catalyst support substrate is called a "coating". It is also possible to apply more than one washcoat to a support substrate. It is known to those skilled in the art that more than one washcoat can be applied to a single support substrate by "layering" or "zoning", and it is also possible to combine layering and zoning. In the case of layering, the washcoats are applied one after the other on the support substrate. The washcoat applied first and thus in direct contact with the support substrate is the "underlayer", and the washcoat applied last is the "upper layer". In the case of zoning, a first washcoat is applied on the support substrate from a first face side A of the support substrate towards the other face side B, but not over the entire length of the support substrate, but only up to the end point between face sides A and B. Then, a second washcoat is applied on the support substrate starting from face side B to the end point between face sides B and A. The end points of the first and second washcoats do not have to be the same, and if they are the same, both washcoat zones are adjacent to each other. However, if the endpoints of two washcoat zones, both located between face sides A and B of the carrier substrate, are not the same, there may be a gap between the first and second washcoat zones or they may overlap. As mentioned above, layering and zoning can also be combined, for example, if one washcoat is applied over the entire length of the carrier substrate and the other washcoat is applied only from one face side to an endpoint between both face sides.

[0036] In the context of this invention, "washcoat loading" is the mass of catalytically active composition per volume of support substrate.

[0037] Those skilled in the art will appreciate that washcoats are prepared in the form of suspensions and dispersions.

[0038] Suspensions and dispersions are heterogeneous mixtures comprising solid particles and a solvent. The solid particles do not dissolve but are suspended throughout the volume of the solvent and remain freely suspended in the medium. If the solid particles have an average particle size of 1 μm or less, the mixture is called a dispersion, and if the average particle size is greater than 1 μm, the mixture is called a suspension. A washcoat in the sense of the present invention comprises a solvent, usually water, suspended or dispersed particles represented by one or more particles of a catalytically active composition, and optionally particles of at least one binder as described above. This mixture is often called a "washcoat slurry". The slurry is applied to a support substrate and subsequently dried to form the coating described above. In the context of the present invention, the term "washcoat suspension" is used for a mixture of a solvent and particles of one or more catalytically active compositions, and optionally particles of at least one binder, regardless of their individual or average particle size. This means that in the "washcoat suspension" of the present invention, the individual particle size as well as the average particle size of the one or more catalytically active solid particles may be less than, equal to and / or greater than 1 μm.

[0039] The term "mixture" as used in the context of the present invention is a material composed of two or more different substances physically combined, in which each component retains its own chemical properties and structure. Despite the fact that there is no chemical change in the components, the physical properties of the mixture, such as its melting point, may differ from those of the components.

[0040] A "catalyzed substrate monolith" is a support substrate comprising a catalytically active composition. The support may be coated with a washcoat comprising the catalytically active composition, the washcoat comprising the catalytically active composition and optionally at least one binder. Alternatively, the catalytically active composition may be a component of the support substrate itself.

[0041] A "device" as used in the context of the present invention is a piece of equipment designed to serve a specific purpose or perform a specific function. A catalytic device according to the present invention serves the purpose and has the function of removing nitrogen oxides from the exhaust gases of a combustion engine. A "device" as used in the present invention may consist of one or more catalysts, also called "catalytic articles" or "bricks", as defined above.

[0042] "Upstream" and "downstream" are terms relative to the normal flow direction of exhaust gases in the exhaust pipe. "Zone or catalyst 1 located upstream of zone or catalyst 2" means that zone or catalyst 1 is located closer to the exhaust gas source, i.e., closer to the motor, than zone or catalyst 2. The flow direction is from the exhaust gas source toward the exhaust pipe. Thus, in this flow direction, exhaust gases enter each zone or catalyst at its inlet end and exit each zone or catalyst at its outlet end.

[0043] As used in the context of the present invention, the term "nitrogen oxides" includes nitric oxide (NO), nitrogen dioxide (NO 2 ) and nitrous oxide (N 2 However, in contrast, nitrous oxide is also an oxide of nitrogen, but is not included in the term "NO x " is NO and NO 2 Contains only N 2 However, "nitrogen oxides" and "NO x This distinction between " and " is widely used by those skilled in the art.

[0044] "NO x The term "conversion rate" as used in the context of the present invention means a NO as defined above. xmeans the percent conversion of nitrogen to

[0045] "N 2 O-selectivity (S N2O ) is the NO in the gas feed x and N.H. 3 N 2 is the percent conversion to O.

[0046] N 2 The O selectivity can be calculated according to the following formula:

number

[0047] Those skilled in the art know that the SCR reaction requires a reducing agent to reduce the nitrogen oxides to nitrogen and water. A suitable reducing agent is ammonia, and the SCR reaction in the presence of ammonia proceeds as described by the reaction "NH 3This is known as "SCR-SCR". The ammonia used as the reducing agent can be made available by feeding liquid or gaseous ammonia or an ammonia precursor compound into the exhaust gas. If an ammonia precursor is used, it is thermally decomposed and hydrolyzed to form ammonia. Examples of such ammonia precursors are ammonium carbamate, ammonium formate, and preferably urea. Alternatively, ammonia may be formed by catalytic reaction of an ammonia precursor in the exhaust gas.

[0048] In an embodiment of the invention, the crystalline aluminosilicate zeolite having a CHA framework structure is selected from the zeotypes SSZ-13, LZ-218, Linde D, Linde R, Phi and ZK-14, with SSZ-13 being preferred.

[0049] The crystalline aluminosilicate having a CHA skeleton structure has an SAR value of 7-25, preferably 9-23, more preferably 11-20, even more preferably 11-17, and most preferably 13-17.

[0050] The crystalline aluminosilicate having a CHA framework structure has a copper content, calculated as CuO, of 3.0% to 4.5% by weight, preferably 3.2% to 4.5% by weight, and more preferably 3.5% to 4.3% by weight, based on the total weight of the zeolite.

[0051] The crystalline aluminosilicate having a CHA framework structure has a manganese content, calculated as MnO, of 0.3 wt. % to 4.0 wt. %, preferably 0.3 wt. % to 3.5 wt. %, and more preferably 0.5 wt. % to 3.2 wt. %, based on the total weight of the zeolite.

[0052] "Total weight of zeolite" is the sum of the weight of white zeolite and the weight of copper and manganese, the weights of copper and manganese being calculated as oxides CuO and MnO, respectively. In the context of the present invention, "white zeolite" refers to TO 4It is an aluminosilicate zeolite with a CHA framework structure, which is composed of tetrahedra and does not contain copper, manganese or any other transition metals. Such zeolites are colorless due to the absence of transition metals, and are also called "white", while transition metals give the zeolite a color, for example, blue when copper is supported, or mixed colors when two or more transition metals, such as copper, are present. Those skilled in the art know that "white zeolites" usually contain protons and alkali metal cations, although often in trace amounts. However, protons and alkali metals do not give the zeolite a color. Therefore, the term "white zeolite" also includes aluminosilicate zeolites with a CHA framework structure that contain protons and alkali metal cations.

[0053] The value (Cu+Mn) / Al obtained by dividing the total molar amount of copper and manganese by the amount of aluminum is within the range of 0.11 to 0.96, preferably 0.20 to 0.80, more preferably 0.28 to 0.35, and even more preferably 0.31 to 0.35.

[0054] The amounts of copper, manganese, aluminum, silicon and, where applicable, sodium, potassium, rubidium, cesium, magnesium, calcium, strontium and barium can be measured by ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy), ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) or XRF (X-ray Fluorescence Spectroscopy). Energy Dispersive X-ray Spectroscopy, known as EDS, EDX or EDXS, allows the analysis of elements with atomic numbers equal to or greater than 8, thereby allowing the above-mentioned purpose and the measurement of oxygen as well. A person skilled in the art knows how to carry out such analyses and can apply this knowledge to the zeolites according to the invention without departing from the scope of the claims.

[0055] The SAR value of a zeolite can be determined by NMR (nuclear magnetic resonance), XRF or ICP-OES. The metal to metal molar ratio in a zeolite, for example the copper to aluminum molar ratio or the copper to manganese molar ratio, can be measured by ICP-OES or XRF. Such methods are known to those skilled in the art and can be applied in the context of the present invention without departing from the scope of the claims.

[0056] Aluminosilicate chabazite and its zeotypes are commercially available. Methods for producing chabazite are disclosed, for example, in EP 2931406 (B1), US 2018 / 079650 (A1), WO 2017 / 080722 (A1), US 2018 / 127282 (A1) and WO 2018 / 189177 (A1). In general, the synthesis of aluminosilicate zeolites includes mixing a silicon source, an aluminum source, an alkali metal or alkaline earth metal hydroxide, water and at least one organic structure directing agent (OSDA), and optionally a salt, such as a copper salt or an iron salt. The mixture forms a gel, which is aged, heat treated, purified, and optionally calcined. Those skilled in the art know how to synthesize the aluminosilicate chabazite and its zeotypes. Some methods for producing aluminosilicate zeolites, particularly CHA, are also known to utilize OSDA, which is a complex of copper with an organic polyamine, such as copper tetraethylenepentamine (Cu-TEPA). When such a complex of copper with an organic polyamine is used, the zeolite obtained therefrom already contains copper. In such cases, the zeolite obtained by synthesis already contains copper. However, in other cases, the synthesis gel does not contain copper.

[0057] In the context of the present invention, the amount of copper and manganese can be adjusted according to the required amount of copper and manganese, and according to the total required molar amount of copper and manganese divided by the molar amount of aluminum, as shown above by the ion exchange method. "Adjusted" means that Cu and Mn can be introduced for the first time if they are not present in the zeolite when synthesized, or their amounts can be increased or decreased if they are introduced during synthesis, but their amounts are outside the range required for the crystalline aluminosilicate according to the present invention. Increasing or decreasing the amount of metals is particularly relevant for copper and manganese, if they are introduced by the synthesis method.

[0058] Copper can be introduced, for example, by ion exchange. In the first step, an ammonium exchange is carried out to replace the alkali metal or alkaline earth metal cation with NH 4 + In the second step, NH 4 + are replaced by copper cations. The copper content of the resulting copper-containing zeolite can be easily controlled by the amount of copper salt and the number of ion exchange procedures carried out. The copper content can be measured by ICP-AES or XRF as described above.

[0059] Copper and manganese are also reacted with NH 4 + It can be removed by liquid ion exchange with cations.

[0060] Methods for introducing ammonium, copper and manganese cations, and methods for removing copper and manganese cations, respectively, are well known to those skilled in the art. These methods can be applied to the zeolite according to the invention without departing from the scope of the claims. For example, ammonium cations can be easily introduced via liquid ion exchange, and copper cations can also be easily introduced via liquid ion exchange, incipient wetness impregnation or solid ion exchange.

[0061] For the introduction of copper cations, methods are presented exemplarily below, which are applicable to obtain zeolites according to the invention loaded with copper and manganese.

[0062] Liquid Ion Exchange NH 4 + Liquid ion exchange involves converting the zeolite into an ammonium salt, e.g., NH 4 Cl or NH 4 NO 3 This can be carried out by treatment with an aqueous solution of

[0063] Cu 2+ Liquid ion exchange involves the exchange of zeolites with copper salts, such as copper acetate (Cu(Ac) 2 ), copper nitrate (Cu(NO 3 ) 2 ), copper acetylacetonate (Cu(acac) 2 ) or copper chloride (CuCl 2 This can be accomplished by treating the copper with an aqueous solution of 0.1% by weight ...

[0064] It is clear to those skilled in the art that the copper to zeolite ratio in the liquid ion exchange can be adjusted according to the desired copper content of the final zeolite. Generally speaking, an aqueous solution with a higher copper content will produce a zeolite with a higher copper content. What copper concentration should be selected and how often the procedure should be repeated can be easily determined by those skilled in the art without departing from the scope of the claims.

[0065] Optionally, the ammonium exchanged zeolite can be heat treated to decompose the ammonium ions, followed by copper exchange as described above.

[0066] Incipient wetness impregnation Copper salts, such as copper acetate (Cu(Ac) 2 ), copper nitrate (Cu(NO3 ) 2 ) or copper chloride (CuCl 2 ) is dissolved in an appropriate volume of water. The amount of copper salt is equal to the amount of copper desired in the zeolite. Incipient wetness impregnation is carried out at room temperature. The copper-exchanged zeolite is then dried at a temperature of 60-70°C for 8-16 hours, and the mixture is subsequently heated to a temperature in the range of 550-900°C.

[0067] Solid Ion Exchange A suitable copper salt is, for example, copper acetate (Cu(Ac) 2 ), copper nitrate (Cu(NO 3 ) 2 ), copper chloride (CuCl 2 ), copper(II) oxide (CuO), copper(I) oxide (Cu 2 O), and copper acetylacetonate (Cu(acac) 2 The copper salt and the zeolite are mixed in the dry state, and the mixture is subsequently heated to a temperature in the range of 550° C. to 900° C. A process for producing metal-containing zeolites is disclosed, for example, in US Patent Application Publication No. 2013 / 0251611 (A1). This method can be applied to the zeolites of the present invention without departing from the scope of the claims.

[0068] The ion exchange method exemplarily described above for exchanging copper and ammonium ions can be applied to the exchange of manganese as well. It is well known that the introduction of different metal ions, for example copper and manganese ions, can be carried out sequentially or by co-ion exchange. Sequential ion exchange means that the different cations are introduced one after the other, for example by introducing copper in a first step and manganese in a second step. Co-ion exchange means that all cations, for example copper and manganese, are exchanged together in one step. Sequential and co-ion exchange can also be applied when three or more different cations, for example copper, manganese and cations of rare earth metals, are to be exchanged. The skilled person knows how to apply the ion exchange method exemplarily described above for the exchange of copper and ammonium ions to the exchange of other ions and can apply this knowledge to the present invention without departing from the scope of the claims.

[0069] A suitable manganese salt for the introduction of manganese by ion exchange is, for example, manganese(II) acetate (Mn(CH 3 COO) 2 ), Manganese(II) acetylacetonate (Mn(acac) 2 ), manganese(III) acetylacetonate (Mn(acac) 3 ), manganese(II) chloride (MnCl 2 ), manganese(II) sulfate (MnSO 4 ) and manganese(II) nitrate (Mn(NO 3 ) 2 ).

[0070] The crystalline aluminosilicate zeolite having a CHA framework according to the present invention is capable of absorbing NO from combustion exhaust gas. x In this process, also known as SCR (selective catalytic reduction), these zeolites can be used in processes for removing NO xThe use of the zeolite according to the invention as a catalytically active composition for converting NOx is therefore applicable to the exhaust gas purification systems of mobile and stationary combustion engines. Mobile combustion engines are, for example, gasoline and diesel engines as well as hydrogen internal combustion engines (H 2 Those skilled in the art know that the combustion process usually occurs under oxidizing conditions and that any fuel contains nitrogen or nitrogen compounds that can be oxidized to NOx, and / or that the combustion occurs in the presence of air, where the oxygen present in the air acts as an oxidant and at least a portion of the nitrogen present therein can be oxidized to NOx.

[0071] The mobile combustion engine may be an engine for on-road and off-road applications, for example, gasoline and diesel engines, and also hydrogen internal combustion engines for passenger cars, agricultural machinery such as farm and forestry tractors and harvesters, construction wheel loaders, bulldozers, highway excavators, forklift trucks, road maintenance equipment, snowplows, ground support equipment at airports, aerial lifts and mobile cranes.

[0072] Stationary combustion engines are, for example, power plants, industrial heaters, cogeneration plants including wood-burning boilers, stationary diesel and gasoline engines, industrial and municipal waste incinerators, industrial drilling rigs, compressors, plants for the production of glass, steel and cement, plants for the production of nitrogen-containing fertilizers, plants for the production of nitric acid (e.g. plants applying the Ostwald process) and ammonia burners for fuelling the gas turbines for the production of nitric acid.

[0073] In a preferred embodiment, the crystalline aluminosilicate small pore zeolites according to the present invention can be used in a process for removing NOx from automotive combustion exhaust gases, the exhaust gases coming from diesel or gasoline engines.

[0074] The object of the present invention is to provide an apparatus for treating exhaust gases from a combustion engine, comprising: x The present invention relates to a method for converting NO x The SCR catalytically active composition for converting is a crystalline aluminosilicate zeolite having a CHA framework according to the present invention.

[0075] In some embodiments of the SCR catalytically active composition according to the invention, the SCR catalytically active composition is present in the form of a coating on a support substrate, i.e., as a washcoat on the support substrate. The support substrate can be so-called honeycomb flow-through substrates and wall-flow filters, as well as corrugated substrates, wound or packed fiber filters, open-cell foams, and sintered metal filters. In a preferred embodiment, the support substrate is a honeycomb flow-through substrate or a honeycomb wall-flow filter.

[0076] The flow-through substrate and wall-flow filter may be made of inert materials such as silicon carbide, aluminum titanate, and cordierite. Such carrier substrates are well known to those skilled in the art and are available on the market. The corrugated substrate is made of ceramic E-glass fiber paper. These are also well known to those skilled in the art and are available on the market.

[0077] When present in the form of a coating on a support substrate, the SCR catalytically active composition is typically present on or in the substrate in an amount of from about 10 g / L to about 600 g / L, preferably from about 100 g / L to about 300 g / L, calculated by weight of molecular sieve per volume of total catalyst article.

[0078] The SCR catalytically active composition can be coated on or to a substrate using known washcoating techniques. In this approach, molecular sieve powder is suspended in a liquid medium along with a binder and stabilizer. A washcoat can then be applied to the surface and walls of the substrate. The washcoat can optionally include TiO2 , SiO 2 , Al 2 O 3 , ZrO 2 , CEO 2 and combinations thereof. The washcoat may further optionally include additives. The additives may be present with the binder as described above, or the washcoat may include only the binder or only the additives. Suitable additives include polysaccharides, polyvinyl alcohols, glycerol; linear or branched polyfunctionalized organic molecules having 2 or more carbon atoms in the chain and up to about 12 carbon atoms (Cn), where 2≦n≦12; salts of basic quaternary amines, where one or more quaternary amine groups are attached to a four carbon chain having a length of Cn, where 1≦n≦5, and the cations include, but are not limited to, the following anions: hydroxide, fluoride, chloride, bromide, iodide, carbonate, sulfate, sulfite, oxalate, maleate, phosphate. , salts of basic quaternary amines, which are balanced as salts with one of the following anions: aluminate, silicate, borate, or other suitable organic or inorganic counter ions; inorganic bases selected from the following list, but not limited to: lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, and barium hydroxide; and simple salts of transition or rare earth elements, including, but not limited to, the rare earth elements with atomic numbers 57 (La) to 71 (Lu) and, as mentioned above, nitrates, carbonates, sulfates, phosphates, borates, such as Sc, Y, Ti, Zr, and Hf.

[0079] In a preferred embodiment, the additive is a polysaccharide selected from the group consisting of galactomannan gum, xanthan gum, guar gum, curdlan, schizophyllan, scleroglucan, diutan gum, welan gum, starch, cellulose or alginates, or is derived from starch, cellulose (i.e. cellulosic) or alginates, and mixtures thereof. The cellulosic additive may be selected from the group consisting of carboxymethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, methylcellulose, methylhydroxyethylcellulose, methylhydroxypropylcellulose and ethylhydroxyethylcellulose.

[0080] More preferably, the additive is xanthan gum, guar gum or a mixture thereof. Even more preferably, the additive is xanthan gum.

[0081] When the first and / or second washcoat includes an additive, the additive is present in an amount of up to 20% by weight, preferably 3% to 15% by weight, more preferably 6% to 10% by weight, based on the total weight of the oxides, where "total weight of oxides" is the sum of the weights of the zeolite and the binder. It will be understood that when the washcoat does not include the binder, the "total weight of oxides" corresponds to the weight of the zeolite.

[0082] In other embodiments, the support substrates may be catalytically active in themselves and may further comprise a catalytically active composition, i.e. a crystalline aluminosilicate zeolite according to the invention. In addition to the catalytically active composition, these support substrates comprise a matrix component. In this context, all inert materials used in other processes for the production of catalytic substrates may be used as matrix components. These are, for example, silicates, oxides, nitrides or carbides, with magnesium aluminum silicate being particularly preferred.

[0083] In another embodiment of the SCR catalytically active composition according to the invention, the catalyst itself forms part of a support substrate, for example as part of a flow-through substrate or a wall-flow filter, such support substrate further comprising the matrix component described above.

[0084] The support substrates containing the SCR catalytically active composition according to the present invention may be used as is for exhaust gas purification. Alternatively, they may be coated with a catalytically active composition, for example, an SCR catalytically active composition. As long as these materials exhibit SCR catalytic activity, the SCR catalytically active compositions mentioned above are suitable materials.

[0085] In one embodiment, the catalytically active support material is produced by mixing 10% to 95% by weight of at least one inert matrix component with 5% to 90% by weight of the catalytically active composition, followed by extrusion of this mixture according to known procedures. As already mentioned above, in this embodiment, inert materials usually used for the production of catalytic substrates may be used as matrix components. Suitable inert matrix materials are, for example, silicates, oxides, nitrides and carbides, with magnesium aluminum silicate being particularly preferred. The catalytically active support material obtained by such a method is known as "extruded catalyzed substrate monolith".

[0086] The application of catalytically active components either onto an inert support substrate or onto a support substrate which is catalytically active alone, as well as the application of catalytically active coatings onto a support substrate, which support substrate comprises a catalyst according to the invention, can be carried out according to manufacturing processes well known to those skilled in the art, for example by the widely used dip-, pump- and suction-coating methods followed by a thermal after-treatment (calcination).

[0087] The skilled person knows that in the case of a wall-flow filter, the average pore size and the average particle size of the catalytically active component according to the invention may be adjusted to one another so that the coating thus obtained is located on the porous walls forming the channels of the wall-flow filter (on-wall coating). However, it is preferred that the average pore size and the average particle size are adjusted to one another so that the catalyst according to the invention is located within the porous walls forming the channels of the wall-flow filter. In this preferred embodiment, the inner surface of the pores is coated (in-wall coating). In this case, the average particle size of the catalyst according to the invention must be small enough to be able to penetrate into the pores of the wall-flow filter. A wall-flow filter coated with an SCR catalytically active composition is also known as "SDPF" (SCR on DPF, i.e. SCR catalytically active composition coated on diesel particulate filter) or "SCRF" (SCR on filter). The invention therefore encompasses a catalyzed substrate monolith, the monolith being a wall-flow filter and the SCR catalytic composition comprising a crystalline aluminosilicate zeolite according to the invention.

[0088] Additionally, the present invention encompasses an ammonia slip catalyst (ASC). In exhaust gas purification systems, appreciable amounts of NH 3 It is well known to those skilled in the art that the ASC is preferably located downstream of the SCR because ammonia exits the SCR based on dynamic operating conditions. Therefore, conversion of excess ammonia exiting the SCR is essential since ammonia is also an emission regulated gas. When ammonia is oxidized, NO is formed as the main product, which then reduces the NOx content throughout the exhaust system. x Therefore, an ASC may be placed downstream of the SCR to further mitigate NO emissions. The ASC catalyst is a catalyst that converts the basic NH 3 It combines oxidation and SCR functions. Ammonia entering the ASC is partially oxidized to NO. As a result, newly oxidized NO and NH in the ASC that have not yet been oxidized3 reacts according to the usual SCR reaction scheme to give N 2 In doing so, the ASC can convert ammonia to N in a parallel mechanism. 2 By doing so, trace amounts of ammonia can be eliminated.

[0089] Those skilled in the art will understand that the SCR catalyst and the ASC catalyst may be present as two consecutive catalyst articles, or the SCR and ASC functional groups may be present on a single catalyst article. In the case of two consecutive catalyst articles, the upstream catalyst article is an SCR catalyst comprising a support substrate and a washcoat comprising an SCR catalytically active composition, and the downstream catalyst article is an ASC catalyst comprising a support substrate, a washcoat comprising an oxidation catalyst, and a washcoat comprising an SCR catalytically active composition. When the SCR catalyst and the ASC catalyst are present on one single substrate, a washcoat comprising the SCR catalytically active composition but not the oxidation catalyst is coated on the upstream zone of the support substrate, and the downstream zone of the support substrate comprises a lower layer having a washcoat comprising an oxidation catalyst and an upper layer having a washcoat comprising the SCR catalytically active composition. In all embodiments in which the SCR catalyst is combined with the downstream ASC catalyst, the SCR catalytically active composition of the SCR catalyst is preferably a crystalline aluminosilicate zeolite according to the present invention. The SCR catalytic active composition of the ASC can be selected from the crystalline aluminosilicate zeolite according to the present invention, the other zeolitic and non-zeolitic molecular sieves mentioned above, and mixed oxides containing vanadia and titania. When other zeolitic and non-zeolitic molecular sieves are used, they are preferably supported with at least one transition metal, preferably copper and / or iron. When a mixed oxide containing vanadia and titania is used, it may also optionally contain oxides of one or more elements selected from tungsten, silicon, aluminum, zirconium, molybdenum, niobium and antimony.

[0090] A platinum group metal may be used as an oxidation catalyst in the ASC and a zeolite may be used for the SCR function. The precious metal is a platinum group metal selected from ruthenium, rhodium, palladium, osmium, iridium, platinum and mixtures thereof. Preferably, the precious metal is selected from palladium, platinum, rhodium and mixtures thereof, more preferably, the precious metal is platinum. In a preferred embodiment, the platinum group metal is added to the washcoat slurry in the form of a precursor salt and applied to the support monolith. The platinum group metal is present in a concentration of 0.01 wt.% to 10 wt.%, preferably 0.05 wt.% to 5 wt.%, even more preferably 0.1 wt.% to 3 wt.%, calculated as the respective platinum group metal, based on the total weight of the washcoat support. In a preferred embodiment, the platinum group metal is platinum, which is present in a concentration of 0.1 wt.% to 1 wt.%, calculated as Pt, based on the total weight of the washcoat support.

[0091] In one embodiment, the ASC catalyst is a catalyzed substrate monolith, the monolith being a flow-through monolith coated with a lower layer comprising an oxidation catalyst and an upper layer comprising a crystalline aluminosilicate zeolite having a CHA framework type according to the present invention.

[0092] It is possible to use one or more of these SCR catalytically active compositions in all devices for the treatment of exhaust gases of combustion engines that contain a crystalline aluminosilicate zeolite according to the invention as an SCR catalytically active composition. If two or more SCR catalytically active compositions are present, they can be present in the form of two or more different layers, two or more different zones, as a mixture of two or more different SCR catalytically active compositions in one washcoat. Furthermore, the layers or zones may, independently of each other, comprise one single SCR catalytically active composition or a mixture of two or more SCR catalytically active compositions. Two or more crystalline aluminosilicate zeolites according to the invention are "different" if they differ in at least one parameter selected from framework type, SAR value, copper content and / or manganese content.

[0093] The present invention further provides an emissions treatment system for removing NOx emissions, and also optionally particulate matter, from an exhaust gas of an internal combustion engine, the system comprising, from upstream to downstream, in the following order: a) means for injecting ammonia or an ammonia precursor solution into the exhaust gas stream; b) a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, the SCR catalytically active composition for converting NOx being a crystalline aluminosilicate zeolite having a CHA framework type according to the present invention, the substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.

[0094] It will be understood by those skilled in the art that if the substrate monolith is a flow-through monolith or a corrugated substrate, the corresponding catalyzed substrate monolith will only remove NOx emissions, however, if the substrate monolith is a wall-flow filter, the corresponding catalyzed substrate monolith will also remove particulate matter.

[0095] Those skilled in the art know that the SCR reaction requires the presence of ammonia as a reducing agent. Ammonia can be provided in a suitable form, for example in the form of liquid ammonia or in the form of an aqueous solution of an ammonia precursor, and can be added to the exhaust gas stream as required via a means for injecting ammonia or an ammonia precursor. Suitable ammonia precursors are, for example, urea, ammonium carbamate and ammonium formate. Alternatively, ammonia can be formed by catalytic reactions in the exhaust gas.

[0096] A widespread method is to deliver an aqueous urea solution and, if necessary, inject it into the catalyst of the present invention via an upstream injector and injection unit. Means for injecting ammonia, such as upstream injectors and injection units, are well known to those skilled in the art and can be used in the present invention without departing from the scope of the claims.

[0097] In addition, NO from the exhaust gas of the internal combustion engine x An exhaust treatment system for removing emissions, and optionally removing particulate matter, the system comprising a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in a vehicle combustion exhaust gas, the NOx being x In one embodiment, the SCR catalytically active composition for converting ethanol into ethanol is a crystalline aluminosilicate zeolite according to the present invention. The system may further include additional catalytic articles, such as a diesel oxidation catalyst (DOC), an ammonia slip catalyst (ASC), a catalyzed or non-catalyzed particulate filter, a passive NOx adsorber (PNA), and / or a lean NOx adsorbent (LNOxA). x It will be appreciated that the catalyzed particulate filter may include a diesel oxidation catalyst, thereby forming a "catalyzed diesel particulate filter (CDPF)" or may be coated with an SCR catalytically active composition, thereby forming an SDPF.

[0098] In one embodiment of the present invention, the emission treatment system including the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located in a proximal coupling position. The term "proximal coupling" refers to the location of the catalytic device in the exhaust gas treatment system of the engine that is less than one meter downstream of the exhaust gas manifold or turbocharger of the engine. In a preferred embodiment, the emission treatment system including the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention further comprises one or more particulate filters. In this embodiment, the "first" filter is the filter located most proximally to the engine. The "second" filter, if present, is located downstream of the first filter, immediately after the first filter or further downstream. In this embodiment, the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located in a proximal coupling position and is located upstream of the first filter.

[0099] As mentioned above, the substrate monolith can be a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam or a sintered metal filter. Preferably, the substrate monolith is a honeycomb flow-through substrate or a honeycomb wall-flow filter. When the catalyzed substrate monolith is a honeycomb wall-flow filter comprising the SCR catalytically active composition according to the present invention, it is referred to as an SDPF.

[0100] In yet another embodiment of the present invention, the emissions treatment system is located in an underfloor position. Underfloor catalyst members are also known in the prior art and are located downstream of any close-coupled and / or mid-coupled catalysts adjacent to the vehicle's muffler or under the vehicle's floor in combination with the vehicle's muffler. In this embodiment, a catalyzed substrate monolith comprising an SCR catalytically active composition according to the present invention is located downstream of the first filter. The substrate monolith comprising an SCR catalytically active composition according to the present invention is the same as described above for the close-coupled configuration.

[0101] In yet another embodiment of the invention, an emissions treatment system comprising a catalyzed substrate monolith comprising an SCR catalytically active composition according to the invention is located upstream of the first particulate filter but more than one meter downstream of the exhaust gas manifold or turbocharger of the engine. In this embodiment, the catalyzed substrate monolith comprising an SCR catalytically active composition according to the invention is preferably the first brick downstream of the exhaust gas manifold or turbocharger of the engine.

[0102] In yet another embodiment of the present invention, an emissions treatment system including a catalyzed substrate monolith comprising an SCR catalytically active composition according to the present invention is disposed downstream of a first particulate filter.

[0103] In those embodiments in which the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located either upstream or downstream of the first particulate filter, the substrate monolith comprising the SCR catalytically active composition according to the present invention is the same as described above for the close-coupled and underfloor configurations.

[0104] The present invention further provides a method for removing NOx emissions, and also optionally particulate matter, from an exhaust gas of an internal combustion engine, the method comprising, from upstream to downstream, in the following order: a) injecting ammonia or an ammonia precursor solution into an exhaust gas stream; and b) introducing the exhaust gas from step a) into a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, the SCR catalytically active composition for converting NOx being a crystalline aluminosilicate zeolite having a CHA framework type according to the present invention, the substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.

[0105] As described above for the emissions treatment system, it will be understood by those skilled in the art that if the substrate monolith used in step b) of the above method is a flow-through monolith or a corrugated substrate, the corresponding catalyzed substrate monolith will only remove NOx emissions. However, if the substrate monolith used in step b) of the above method is a wall-flow filter, the corresponding catalyzed substrate monolith will also remove particulate matter. [Brief description of the drawings]

[0106] [Figure 1] 1 shows the percent NOx conversion in a standard SCR reaction ("NO" only) in the fresh state for Comparative Example 1 and Examples 1, 2, 3 and 4. [Diagram 2] 2 shows the NO concentration (ppm) in the standard SCR reaction ("NO only") in the fresh state for Comparative Example 1 and Examples 1, 2, 3 and 4. [Diagram 3] The N2O selectivity (percent) for the standard SCR reaction in the fresh state ("NO only") and with 25% and 50% NO2 is shown for Comparative Example 1 and Examples 1, 2, 3 and 4. [Figure 4] The N2O selectivity (percent) for the standard SCR reaction ("NO only") and with 25% and 50% NO2 in the aged state is shown for Comparative Example 1 and Examples 1, 2, 3, and 4. Aging was performed at 750°C for 16 hours. [Diagram 5] The NOx conversion (percent) in a standard SCR reaction ("NO" only) in the aged state is shown for Comparative Example 1 and Examples 1, 2, 3 and 4. Aging was performed at 750° C. for 16 hours. [Figure 6] The NO concentration (ppm) in the standard SCR reaction ("NO only") in the aged state is shown for Comparative Example 1 and Examples 1, 2, 3, and 4. Aging was performed at 750°C for 16 hours. [Figure 7]1 shows the NOx conversion (percent) in a fresh NO-only SCR reaction at 180° C. for Comparative Example 2 and Examples 5, 6, 7, 8 and 9. [Figure 8] For Comparative Example 2 and Examples 5, 6, 7, 8 and 9, the N2O concentration (ppm) in the SCR reaction using only NO at 250°C in a fresh state is shown. [Figure 9] Fresh Delta NOx, i.e., the NOx conversion (percent) in the SCR reaction with 50% NO2 at 180°C for Examples 5-9 minus the corresponding NOx conversion for Comparative Example 2, is shown. [Figure 10] 1 shows delta N2O in the fresh state, i.e., N2O formation (ppm) in the SCR reaction with 50% NO2 at 250°C in Comparative Example 2 minus the corresponding N2O formation in Examples 5-9. [Figure 11] The percent NOx conversion in an NO-only SCR reaction at 180° C. in the aged state is shown for Comparative Example 2 and Examples 5, 6, 7, 8 and 9. Aging was performed at 750° C. for 16 hours. [Figure 12] The figure shows the NO concentration (ppm) in the SCR reaction with only NO at 250° C. in the aged state for Comparative Example 2 and Examples 5, 6, 7, 8 and 9. Aging was performed at 750° C. for 16 hours. [Figure 13] The figures show delta NOx in the aged state, i.e., the NOx conversion (percent) in the SCR reaction with 50% NO2 at 180°C for Examples 5-9 minus the corresponding NOx conversion for Comparative Example 2. Aging was performed at 750°C for 16 hours. [Figure 14] Delta N2O in the aged state, i.e., N2O formation (ppm) in the SCR reaction with 50% NO2 at 250°C for Comparative Example 2 minus the corresponding N2O formation for Examples 5 to 9. Aging was performed at 750°C for 16 hours.

[0107] Embodiment Preparation of powders for Comparative Example 1, Comparative Example 2 and Examples 1-9: H + A purchased zeolite powder of the CHA framework structure with SAR 13 was used as the base zeolite material. 1.2 kg of the base zeolite was added with Cu(NO 3 ) 2 The powder was impregnated with an aqueous solution of Cu(NO 3 ) 2 The aqueous solution was prepared by mixing 540 g of deionized water and 122.1 g of Cu(NO 3 ) 2 *3H 2 The Cu salt was prepared from a mixture of Cu and O, and the Cu salt was completely dissolved before being added to the zeolite powder. After impregnation, the Cu-loaded zeolite was dried at 120 °C for 8 h and calcined at 600 °C for 2 h.

[0108] To prepare the powders of Examples 1 to 4, 122.1 g of Cu(NO 3 ) 2 *3H 2 O and Mn(NO 3 ) 2 The aqueous solution containing the solution was mixed with deionized water to a total water amount of 540 g. In Examples 1 to 4, the values ​​of X are 46.2 g, 92.3 g, 138.5 g, and 184.7 g, respectively.

[0109] The powders of Comparative Example 2 (CE2) and Examples 5 to 9 (Ex5 to Ex9) were prepared in the same manner as in Examples 1 to 4. The results are shown in Table 1. Comparative Example 2 corresponds to Example 1g of US Patent Application Publication No. 2015 / 078989(A1).

[0110] Preparation of coated catalysts of Comparative Example 1 and Examples 1-4: The powders prepared for Comparative Example 1 and Examples 1-4 were each coated onto individual commercially available extruded monolithic carrier materials with dimensions of 5.66 inches in diameter and 3.0 inches in length, channel dimensions of 400 cpsi, and wall thickness of 4 mils. 2 O, Al as a binder 2 O3 A slurry of the prepared Cu / Mn-zeolite powder was mixed and left to stir overnight. A commercial monolithic support was submerged in the slurry and then dried by hot air flow. This process was repeated until the loading of the dried coating reached 150 g / L. [Table 1]

[0111] Aging, NOx conversion rate and N 2 Measurement of O formation The coated catalyst was cooled in a hydrothermal atmosphere (10% H 2 O, 10% O 2 , remaining N 2 The measurements were performed after aging in a hydrothermal atmosphere for 16 hours at 750°C.

[0112] In the so-called NOx conversion test, the NOx conversion of the catalyst as a function of the temperature upstream of the catalyst is x The conversion was determined in a model gas reactor.

[0113] The NOx conversion test consists of a test procedure that includes pretreatment and test cycles conducted to various target temperatures.

[0114] Test procedure: 1. N at 600°C for 10 min 2 Pre-conditioning in 2. Repeat the test cycle to the target temperature a. Approaching the target temperature in gas mixture 1 b.NO x Add (Gas Mixture 2) c.NH 3 (Gas Mixture 3) was added and NH 3 Wait until it exceeds 20 ppm or for a maximum of 30 minutes d. Temperature programmable desorption at up to 500°C (Gas Mixture 3)

[0115] Measurement of NO only (Table 2a), NO with NOx concentration of 25% 2 (Table 2b) and NOx concentration of 50% 2 In the case of measurements using (Table 2c), the NOx concentrations in the gas compositions in test procedure ranges 3 and 4 are adjusted accordingly. [Table 2] [Table 3] [Table 4]

[0116] At all temperatures, the gas hourly space velocity (GHSV) for the catalyst measurements was 60,000 h. -1 It was.

[0117] For each temperature point below 500°C, 20 ppm NH 3 The conversion at slip is determined for the test procedure range 2c. The conversion at equilibrium is determined for the temperature point at 500° C. in the test procedure range 2c. This NOx conversion is plotted against the various temperature points, resulting in the plots shown in FIGS. 1 and 3.

[0118] The following table shows the NO shown in Table 2a to Table 2c. x Conversion rate test condition NOx conversion rate (percent), N 2 O concentration (ppm) and N 2 O selectivity (%) is shown.

[0119] CE1 = Comparative Example 1, Ex1 to Ex4 = Examples 1 to 4 [Table 5] [Table 6] [Table 7] [Table 8]

[0120] The data in Tables 3 to 6 show that the CHA aluminosilicate zeolite of the present invention, in a fresh state, x Conversion rate and N 2 This shows a disproportionate reduction in N2O3 formation in the CHA zeolite of the present invention in the fresh state. 2 O formation was significantly reduced compared to the corresponding NO x This means that the conversion rate is decreased more than that of the NO 3 zeolite. x The conversion rate increases and at the same time N 2 This indicates that O formation is reduced.

[0121] Aging, NOx conversion rate and N 2 Measurement of O formation NO in Comparative Example 2 and Examples 5 to 9 x The conversion was measured at 180° C. for the fresh and aged states of the catalyst powder.

[0122] N 2 O formation was measured at 250° C. in the fresh and aged states of the catalyst powder.

[0123] The measurements were carried out using a conventional plug flow model, in which a gas flow simulating lean-burn exhaust gas from an engine was passed over and through mesh particles of the test samples under various temperature conditions, and the effectiveness of the samples in reducing NOx was determined by an online FTIR (Fourier Transform Infrared) spectrometer.

[0124] Table 7 below details the complete experimental parameters used in generating the data contained herein. [Table 9]

[0125] The results are shown in Figures 8 and 9.

[0126] "Delta NO x " is the number of Examples 5 to 9 x The corresponding value of the conversion rate is x It was calculated by subtracting the conversion rate values.

[0127] "Delta N 2 "O" is the N of CE2 2 From the corresponding values ​​of O formation, N 2 The calculation was performed by subtracting the value of O formation.

[0128] The positive delta values ​​indicate that each of the Examples Ex5-Ex9 has better NOx conversion or less NOx than CE2. 2 Negative delta values ​​indicate that CE2 exhibits better NO2 formation than Ex5-Ex9, respectively. x Conversion rate or less N 2 This indicates that O formation is present.

[0129] The results are shown in Figures 7 to 14. [Table 10] [Table 11]

Claims

1. 1. A catalytically active composition comprising a crystalline aluminosilicate zeolite having a CHA framework type, said zeolite having an SAR value of 7 to 25, a copper content of 3.0% to 4.5% by weight, and a manganese content of 0.3% to 4.0% by weight, said copper and said manganese being calculated as CuO and MnO based on the total weight of said zeolite, and the sum of the molar amounts of copper and manganese divided by the molar amount of aluminum is in the range of 0.11 to 0.

96.

2. 2. The catalytically active composition of claim 1, wherein the crystalline aluminosilicate having a CHA framework structure is selected from zeotypes SSZ-13, LZ-218, Linde D, Linde R, Phi and ZK-14.

3. 2. The catalytically active composition of claim 1, wherein the crystalline aluminosilicate having a CHA framework structure has an SAR value of 10-23.

4. 2. The catalytically active composition of claim 1, wherein the crystalline aluminosilicate having a CHA framework structure has a copper content, calculated as CuO, of 3.3% to 3.7% by weight, based on the total weight of the zeolite.

5. 2. The catalytically active composition of claim 1, wherein the crystalline aluminosilicate having a CHA framework structure has a manganese content, calculated as MnO, of 0.6% to 4.0% by weight, based on the total weight of the zeolite.

6. 2. The catalytically active composition of claim 1, wherein the sum of the molar amounts of copper and manganese divided by the amount of aluminum is in the range of 0.25 to 0.

40.

7. NO from combustion exhaust gas x A process for removing NO, comprising the steps of: x The process according to claim 1, wherein the active composition is used as an SCR catalyst for converting

8. NO for use in the treatment of automotive combustion exhaust gases x A catalyzed substrate monolith comprising an SCR catalytically active composition for converting NO x 13. A catalyzed substrate monolith, wherein the SCR catalytically active composition for converting

9. 9. The catalyzed substrate monolith of claim 8, wherein the crystalline aluminosilicate zeolite is present in the form of a washcoat on a support substrate.

10. 9. The catalyzed substrate monolith of claim 8, wherein the support substrate is a flow-through substrate, a wall-flow filter, or a corrugated substrate.

11. 9. The catalyzed substrate monolith of claim 8, wherein the catalyzed substrate monolith is an extruded catalyzed substrate monolith.

12. 10. The catalyzed substrate monolith of claim 9, wherein the monolith is a flow-through monolith coated with a lower layer comprising an oxidation catalyst and an upper layer comprising the crystalline aluminosilicate zeolite having the CHA framework type of claim 1.

13. NO from the exhaust gas of an internal combustion engine x 1. An emission treatment system for removing emissions, and optionally also removing particulate matter, said system comprising, from upstream to downstream, in the following order: a) a means for injecting ammonia or an ammonia precursor solution into the exhaust gas stream; b) a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, said SCR catalytically active composition for converting NOx being a crystalline aluminosilicate zeolite having a CHA framework type according to any one of claims 1 to 6, said substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.

14. The waste treatment system of claim 13 , wherein the waste treatment system is disposed in a proximal coupling position.

15. The emissions treatment system of claim 13 , wherein the emissions treatment system is located in an under-floor location.

16. NO from the exhaust gas of an internal combustion engine x 1. A process for removing emissions, and optionally also particulate matter, comprising, from upstream to downstream, in the following order: a) injecting ammonia or an ammonia precursor solution into an exhaust gas stream; and b) introducing the exhaust gas from step a) into a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, said SCR catalytically active composition for converting NOx being a crystalline aluminosilicate zeolite having a CHA framework type according to any one of claims 1 to 6, said substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.

17. The internal combustion engine is a gasoline, diesel and hydrogen internal combustion engine (H 2 17. The method of claim 16, wherein the ICE is selected from the group consisting of: